2019
DOI: 10.1002/maco.201911257
|View full text |Cite
|
Sign up to set email alerts
|

Mn‐promoting formation of a long‐period stacking‐ordered phase in laser‐melted Mg alloys to enhance degradation resistance

Abstract: Magnesium (Mg) alloys are promising candidates for use as biomedical implant materials. However, their very fast degradation rate greatly restricts their application. A rare earth phase possessed with a long‐period stacking‐ordered (LPSO) structure was in favor of enhancing the degradation resistance of Mg alloys. In fact, the formation of the LPSO phase in Mg alloys depends on their stacking fault energy. The lower the stacking fault energy, the more the LPSO phase formed. In this study, manganese (Mn) was al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…Chemical composition of material is another key factor affecting grain size. Up to now, the effects of Al [43,79], Mn [93][94][95], Zn [44], Cu [92,96], Ce [97], Dy [98] on the grain size of additively manufactured magnesium alloys have been investigated. The results demonstrated that the addition of Al, Cu, Zn, Ce and Dy can significantly refine the grains, and the grain size decreases monotonically with the content increase of these elements.…”
Section: Microstructure Characteristicsmentioning
confidence: 99%
See 4 more Smart Citations
“…Chemical composition of material is another key factor affecting grain size. Up to now, the effects of Al [43,79], Mn [93][94][95], Zn [44], Cu [92,96], Ce [97], Dy [98] on the grain size of additively manufactured magnesium alloys have been investigated. The results demonstrated that the addition of Al, Cu, Zn, Ce and Dy can significantly refine the grains, and the grain size decreases monotonically with the content increase of these elements.…”
Section: Microstructure Characteristicsmentioning
confidence: 99%
“…Higher SFE leads to easier formation of LPSO structure. Shuai et al found that Mn addition could lower the SFE of ZK30-10Gd alloy and promote the precipitation of LPSO structure in as-built LPBF microstructure [95]. However, the precipitation behavior of LPSO structure was still not adequate during the LPBF process.…”
Section: Phase Constituentmentioning
confidence: 99%
See 3 more Smart Citations